The Concept of an Ideal Urban Forest and Its Role as a Sustainable Educational Tourism Destination: A Case Study of Pekanbaru Urban Forest - Muhammad Hifzil; Rina Novia Yanti; Dodi Sukma RA (CV. AFDIFAL MAJU BERKAH, 2026)
Urban forests are strategic components of urban green space systems because they provide ecological, recreational, and educational functions that collectively support sustainable urban environmental quality. This study aims to formulate an ideal model of an urban forest concept as a sustainable educational tourism site based on empirical findings derived from visitor perceptions and the ecological conditions of the Pekanbaru Urban Forest. The research employed a simple mixed-method approach dominated by descriptive quantitative analysis involving 96 respondents, complemented by ecological observations and in-depth interviews with site managers. The results indicate that cleanliness and comfort received positive assessments (scores 4.21 and 4.12), whereas environmental education facilities (3.88), educational activities (3.45), and promotional efforts (3.22) fell within the moderate to low categories. These findings highlight a significant gap between the ecological potential of the area and the development of its educational functions. A synthesis of empirical data and theoretical insights produced six components of the ideal urban forest concept: (1) adaptive ecology, (2) environmental education facilities, (3) interpretive trails, (4) sustainable educational tourism programs, (5) inclusive accessibility, and (6) collaborative governance. Policy analysis further demonstrates that strengthening the educational function aligns with the mandates of Law No. 26/2007 on Spatial Planning, SDG 11.7 targets regarding inclusive green spaces, and the Pekanbaru Strategic Environmental Assessment (KLHS) emphasizing the enhancement of environmental quality. This study concludes that the integration of ecological planning, educational development, and collaborative governance forms the essential foundation for positioning urban forests as centers of sustainable environmental learning